An Experimental Intervention Study Assessing the Impact of a Thin Silicone Gel Surface Overlay on Interface Pressure. (25th November 2020) - Angmorterh, Seth Kwadjo; England, Andrew; Aboagye, Sonia; Ofori, Eric Kwasi; Hogg, Peter
Abstract : Introduction . The incidence of pressure ulcers (PUs) presents a substantial threat to patients, especially geriatric patients, those with restricted mobility, and patients suffering from chronic diseases such as cancer. PUs creates a huge financial burden on healthcare authorities and patients, costing billions to treat and manage. Radiography and radiotherapy patients may experience medical device related (MDR) PUs and studies have shown that high interface pressure (IP) values exist for the head when placed on an X-ray table without a mattress. These high IP values pose a PU risk to patients, especially those accessing prolonged radiography/radiology and radiotherapy procedures. The current study assessed the impact on IP values for the head from using a thin silicone gel surface overlay during radiographic procedures and identified whether this reduced the risk of PUs. Materials and Methods . A calibrated XSENSOR pressure mat was used to measure IP for the head on an X-ray table with and without a thin silicone gel surface overlay. Prior to pressure mapping, the silicone gel surface overlay was assessed for its impact on radiation attenuation and image quality. Results . Study participants were 14 males (70%) and six females (30%), with an age range of 25–53 years (mean = 34.4 ± 7.0). Paired-samples t -test results indicated that there was a statistically significant decrease in the mean IP for the head on the X-ray table without the silicone gel surface overlay (mean = 83.9 ± 8.2 in mmHg) and the X-ray table with the gel surface overlay (mean = 62.4 ± 6.1 in mmHg), p ≤ 0.001 . Paired-samples t -test results indicated that there was a statistically significant decrease in the mean peak pressure index (PPI) for the head on the X-ray table without the silicone gel surface overlay (mean = 205.1 ± 28.2 in mmHg) and the X-ray table with the gel surface overlay (mean = 159.8 ± 26.8 in mmHg), p ≤ 0.001 . Conclusions . The use of a thin silicone gel surface overlay could reduce IP risk for the head by approximately 25%. The reduction in IP risk could have a significant impact in reducing the risk of developing a PU. To ensure maximum benefit, the silicone gel surface overlay should be evaluated to address the specific needs within radiography and radiotherapy planning and treatment settings.